Utilization of Music Therapy as a Complementary Intervention for Type 2 Diabetes Mellitus Patients in the Community - hidayah, nurul; Budiono, Budiono; Utomo, Agus Setyo (Jurnal IDAMAN (Induk Pemberdayaan Masyarakat Pedesaan), 2026)
Diabetes mellitus (DM) is a chronic metabolic disease associated with high clinical and psychosocial burden, requiring consistent self-management. Psychological distress and poor sleep quality are common among patients with type 2 DM and may negatively affect glycemic control. Music therapy, as a complementary intervention, is considered safe, affordable, and easy to implement in community settings. This community service program aimed to implement a music therapy intervention and evaluate its short-term effects on distress, sleep quality, and capillary blood glucose levels in patients with type 2 DM. A quasi-experimental one-group pretest-posttest design was used. A total of 36 participants were recruited using purposive sampling. The intervention consisted of guided music listening combined with breathing exercises, conducted over four weeks (eight group sessions and daily independent practice). The results showed a decrease in distress scores, improvement in sleep quality, and a reduction in average capillary blood glucose levels after the intervention. These findings indicate that music therapy has the potential to support psychological well-being and metabolic control in patients with DM. In conclusion, music therapy is a feasible and acceptable complementary intervention that can be integrated into community-based diabetes management programs. Further studies with control groups and longer follow-up are recommended.